An evaluation of the exposure in nadir observation of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Ambrosio, M.; Anchordoqui, L.; Anzalone, Anna; Arai, Y.; Aramo, Carla; Asano, K.; Ave, M.; Barrillon, P.; et al. (Astroparticle Physics, 2013)
We evaluate the exposure during nadir observations with JEM-EUSO, the Extreme Universe Space Observatory, on-board the Japanese Experiment Module of the International Space Station. Designed as a mission to explore the extreme energy Universe from space, JEM-EUSO will monitor the Earth's nighttime atmosphere to record the ultraviolet light from tracks generated by extensive air showers initiated by ultra-high energy cosmic rays. In the present work, we discuss the particularities of space-based observation and we compute the annual exposure in nadir observation. The results are based on studies of the expected trigger aperture and observational duty cycle, as well as, on the investigations of the effects of clouds and different types of background light. We show that the annual exposure is about one order of magnitude higher than those of the presently operating ground-based observatories. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ultra High Energy Cosmic Rays; Space-based experiment; Extensive air showers; JEM-EUSO mission

An overview of the JEM-EUSO program and results - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
The field of UHECRs (Ultra-High energy cosmic Rays) and the understanding of particle acceleration in the cosmos, as a key ingredient to the behaviour of the most powerful sources in the universe, is of outmost importance for astroparticle physics as well as for fundamental physics and will improve our general understanding of the universe. The current main goals are to identify sources of UHECRs and their composition. For this, increased statistics is required. A space-based detector for UHECR research has the advantage of a very large exposure and a uniform coverage of the celestial sphere. The aim of the JEM-EUSO program [1] is to bring the study of UHECRs to space. The principle of observation is based on the detection of UV light emitted by isotropic fluorescence of atmospheric nitrogen excited by the Extensive Air Showers (EAS) in the Earth's atmosphere and forward-beamed Cherenkov radiation reflected from the Earth's surface or dense cloud tops. In addition to the prime objective of UHECR studies, JEM-EUSO will do several secondary studies due to the instruments' unique capacity of detecting very weak UV-signals with extreme time-resolution around 1 μs: meteors, Transient Luminous Events (TLE), bioluminescence, maps of human generated UV-light, searches for Strange Quark Matter (SQM) and high-energy neutrinos, and more. The JEM-EUSO program includes several missions from ground (EUSO-TA [2]), from stratospheric balloons (EUSO-Balloon [3], EUSO-SPB1 [4], EUSO-SPB2 [5]), and from space (TUS [6], Mini-EUSO [7]) employing fluorescence detectors to demonstrate the UHECR observation from space and prepare the large size missions K-EUSO [8] and POEMMA [9]. A review of the current status of the program, the key results obtained so far by the different projects, and the perspectives for the near future are presented.
CRIS-Team Scopus Importer:2024-12-16

A Review of the EUSO-Balloon Pathfinder for the JEM-EUSO Program - Adams, J. H.; Ahmad, S.; Allard, D.; Anzalone, A.; Bacholle, S.; Barrillon, P.; Bayer, J.; Bertaina, M.; Bisconti, F.; Blaksley, C.; Blin-Bondil, S.; Bobik, P.; et al. (Space Science Reviews, 2022)
EUSO-Balloon is a pathfinder for JEM-EUSO, the mission concept of a spaceborne observatory which is designed to observe Ultra-High Energy Cosmic Ray (UHECR)-induced Extensive Air Showers (EAS) by detecting their UltraViolet (UV) light tracks "from above." On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. After reaching a floating altitude of 38 km, EUSO-Balloon imaged the UV light in the wavelength range similar to 290-500 nm for more than 5 hours using the key technologies of JEM-EUSO. The flight allowed a good understanding of the performance of the detector to be developed, giving insights into possible improvements to be applied to future missions. A detailed measurement of the photoelectron counts in different atmospheric and ground conditions was achieved. By means of the simulation of the instrument response and by assuming atmospheric models, the absolute intensity of diffuse light was estimated. The instrument detected hundreds of laser tracks with similar characteristics to EASs shot by a helicopter flying underneath. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. The reconstruction of the direction of the laser tracks was performed. In this work, a review of the main results obtained by EUSO-Balloon is presented as well as implications for future space-based observations of UHECRs.
CRIS-Team WoS Importer:2022-02-11

A study on UV emission from clouds with Mini-EUSO - Golzio, Alessio; Battisti, Matteo; Bertaina, Mario; Bolmgren, Karl; Cambiè, Giorgio; Casolino, Marco; Cassardo, Claudio; Cremonini, Roberto; Ferrarese, Silvia; Fuglesang, Christer; Manfrin, Massimiliano; Marcelli, Laura; et al. (Proceedings of 37th International Cosmic Ray Conference – PoS(ICRC2021), 2022)
Mini-EUSO is the first mission of the JEM-EUSO program located on the International Space Station. One of the main goals of the mission is to provide valuable scientific data in view of future large missions devoted to study Ultra-High Energy Cosmic Rays (UHECRs) from space by exploiting the fluorescence emission generated by Extensive Air Showers (EAS) developing in the atmosphere. A space mission like Mini-EUSO experiences continuous changes in atmospheric conditions, including the cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate as it might alter the instantaneous exposure for EAS detection or deteriorate the quality of the EAS images with consequences on the reconstructed EAS parameters. For this purpose, JEM-EUSO is planning to have an IR camera and a lidar as part of its Atmospheric Monitoring System. At the same time, it would be extremely beneficial if the UV camera itself would be able to detect the presence of clouds, at least in some specific conditions. For this reason, we analyze a few case studies by comparing the pixel count rates from Mini-EUSO during orbits with the cloud cover (as cloud fraction). This quantity is retrieved from the Global Forecast System (GFS) model at different height levels over the Mini-EUSO trajectory. The results of this analysis are reported.
CRIS-Team Scopus Importer:2022-12-23

Calibration aspects of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will be, after calibration, a very accurate instrument which yields the number of received photons from the number of measured photo-electrons. The project is in phase A (demonstration of the concept) including already operating prototype instruments, i.e. many parts of the instrument have been constructed and tested. Calibration is a crucial part of the instrument and its use. The focal surface (FS) of the JEM-EUSO telescope will consist of about 5000 photo-multiplier tubes (PMTs), which have to be well calibrated to reach the required accuracy in reconstructing the air-shower parameters. The optics system consists of 3 plastic Fresnel (double-sided) lenses of 2.5 m diameter. The aim of the calibration system is to measure the efficiencies (transmittances) of the optics and absolute efficiencies of the entire focal surface detector. The system consists of 3 main components: (i) Pre-flight calibration devices on ground, where the efficiency and gain of the PMTs will be measured absolutely and also the transmittance of the optics will be. (ii) On-board relative calibration system applying two methods: a) operating during the day when the JEM-EUSO lid will be closed with small light sources on board. b) operating during the night, together with data taking: the monitoring of the background rate over identical sites. (iii) Absolute in-flight calibration, again, applying two methods: a) measurement of the moon light, reflected on high altitude, high albedo clouds. b) measurements of calibrated flashes and tracks produced by the Global Light System (GLS). Some details of each calibration method will be described in this paper.
Keywords: Air-Shower fluorescence telescope; JEM-EUSO; Calibration; Space-Based experiment

Cosmic ray oriented performance studies for the JEM-EUSO first level trigger - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
JEM-EUSO is a space mission designed to investigate Ultra-High Energy Cosmic Rays and Neutrinos (E > 5.10(19) eV) from the International Space Station (ISS). Looking down from above its wide angle telescope is able to observe their air showers and collect such data from a very wide area. Highly specific trigger algorithms are needed to drastically reduce the data load in the presence of both atmospheric and human activity related background light, yet retain the rare cosmic ray events recorded in the telescope. We report the performance in offline testing of the first level trigger algorithm on data from JEM-EUSO prototypes and laboratory measurements observing different light sources: data taken during a high altitude balloon flight over Canada, laser pulses observed from the ground traversing the real atmosphere, and model landscapes reproducing realistic aspect ratios and light conditions as would be seen from the ISS itself. The first level trigger logic successfully kept the trigger rate within the permissible bounds when challenged with artificially produced as well as naturally encountered night sky background fluctuations and while retaining events with general air-shower characteristics. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: JEM-EUSO; Trigger system; FPGA; Nightglow background

EUSO-SPB1 mission and science - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Pernas, M. Ave; et al. (Astroparticle Physics, 2024)
The Extreme Universe Space Observatory on a Super Pressure Balloon 1 (EUSO-SPB1) was launched in 2017 April from Wanaka, New Zealand. The plan of this mission of opportunity on a NASA super pressure balloon test flight was to circle the southern hemisphere. The primary scientific goal was to make the first observations of ultra-high-energy cosmic-ray extensive air showers (EASs) by looking down on the atmosphere with an ultraviolet (UV) fluorescence telescope from suborbital altitude (33 km). After 12 days and 4 h aloft, the flight was terminated prematurely in the Pacific Ocean. Before the flight, the instrument was tested extensively in the West Desert of Utah, USA, with UV point sources and lasers. The test results indicated that the instrument had sensitivity to EASs of ⪆3 EeV. Simulations of the telescope system, telescope on time, and realized flight trajectory predicted an observation of about 1 event assuming clear sky conditions. The effects of high clouds were estimated to reduce this value by approximately a factor of 2. A manual search and a machine-learning-based search did not find any EAS signals in these data. Here we review the EUSO-SPB1 instrument and flight and the EAS search.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Air fluorescence; Cosmic rays (329); Extensive air showers; High-altitude balloons (738); JEM-EUSO

EUSO-SPB2 Telescope Optics and Testing - Kungel, Viktoria; Bachman, Randy; Brewster, Jerod; Dawes, Madeline; Desiato, Julianna; Eser, Johannes; Finch, William; Huelett, Lindsey; Olinto, Angela V.; Pace, Justin; Pech, Miroslav; Reardon, Patrick; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory - Super Pressure Balloon (EUSO-SPB2) mission will fly two custom telescopes that feature Schmidt optics to measure Čerenkov- and fluorescence-emission of extensive air-showers from cosmic rays at the PeV and EeV-scale, and search for τ-neutrinos. Both telescopes have 1-meter diameter apertures and UV/UV-visible sensitivity. The Čerenkov telescope uses a bifocal mirror segment alignment, to distinguish between a direct cosmic ray that hits the camera versus the Čerenkov light from outside the telescope. Telescope integration and laboratory calibration will be performed in Colorado. To estimate the point spread function and efficiency of the integrated telescopes, a test beam system that delivers a 1-meter diameter parallel beam of light is being fabricated. End-to-end tests of the fully integrated instruments will be carried out in a field campaign at dark sites in the Utah desert using cosmic rays, stars, and artificial light sources. Laser tracks have long been used to characterize the performance of fluorescence detectors in the field. For EUSO-SPB2 an improvement in the method that includes a correction for aerosol attenuation is anticipated by using a bi-dynamic Lidar configuration in which both the laser and the telescope are steerable. We plan to conduct these field tests in Fall 2021 and Spring 2022 to accommodate the scheduled launch of EUSO-SPB2 in 2023 from Wanaka, New Zealand.
CRIS-Team Scopus Importer:2024-12-16

EUSO-TA - First results from a ground-based EUSO telescope - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2018)
EUSO-TA is a ground-based telescope, installed at the Telescope Array (TA) site in Black Rock Mesa, Utah, USA. This is the first detector to successfully use a Fresnel lens based optical system and multi-anode photomultipliers (64 channels per tube, 2304 channels encompassing a 10.6 degrees x 10.6 degrees field of view) for detection of Ultra High Energy Cosmic Rays (UHECR). The telescope is located in front of one of the fluorescence detectors of the TA experiment. Since its installation in 2013, the detector has observed several ultra-high energy cosmic ray events and, in addition, meteors. The limiting magnitude of 5.5 on summed frames (similar to 3 ms) has been established. Measurements of the UV night sky emission in different conditions and moon phases and positions have been completed. The performed observations serve as a proof of concept for the future application of this detector technology. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: UHECR; EAS; JEM-EUSO; cosmic rays; Fresnel lens

Expected Performance of the EUSO-SPB2 Fluorescence Telescope - Heaton, C.; Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory Super Pressure Balloon 2 (EUSO-SPB2) is under development, and will prototype instrumentation for future satellite-based missions, including the Probe of Extreme Multi-Messenger Astrophysics (POEMMA). EUSO-SPB2 will consist of two telescopes. The first is a Cherenkov telescope (CT) being developed to identify and estimate the background sources for future below-the-limb very high energy (E>10 PeV) astrophysical neutrino observations, as well as above-the-limb cosmic ray induced signals (E>1 PeV). The second is a fluorescence telescope (FT) being developed for detection of Ultra High Energy Cosmic Rays (UHECRs). In preparation for the expected launch in 2023, extensive simulations tuned by preliminary laboratory measurements have been performed to understand the FT capabilities. The energy threshold has been estimated at 1018.2 eV, and results in a maximum detection rate at 1018.6 eV when taking into account the shape of the UHECR spectrum. In addition, onboard software has been developed based on the simulations as well as experience with previous EUSO missions. This includes a level 1 trigger to be run on the computationally limited flight hardware, as well as a deep learning based prioritization algorithm in order to accommodate the balloon's telemetry budget. These techniques could also be used later for future, space-based missions.
CRIS-Team Scopus Importer:2024-12-16

Expected performance of the K-EUSO space-based observatory - Bianciotto, Marta; Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; et al. (Proceedings of Science, 2022)
K-EUSO is a planned mission of the JEM-EUSO program for the study of ultra-high energy cosmic rays (UHECR) from space, to be deployed on the International Space Station. The K-EUSO observatory consists of a UV telescope with a wide field of view, which aims at the detection of fluorescence light emitted by extensive air showers (EAS) in the atmosphere. The EAS events will be sampled with a time resolution of 1-2.5 μs to reconstruct the entire shower profile with high precision. The detector consisting of ∼ 105 independent pixels will allow a spatial resolution of ∼700 m on ground. From a 400 km altitude, K-EUSO will achieve a large and full sky exposure to sample the highest energy range of the UHECR spectrum. In this contribution, we present estimates of the performance of the observatory: an estimation of the expected exposure and triggered event rate as a function of energy and the event reconstruction performance, including resolution of arrival directions and energy of UHECRs.
CRIS-Team Scopus Importer:2024-12-16

First observations of speed of light tracks by a fluorescence detector looking down on the atmosphere - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Journal of Instrumentation, 2018)
EUSO-Balloon is a pathfinder mission for the Extreme Universe Space Observatory onboard the Japanese Experiment Module (JEM-EUSO). It was launched on the moonless night of the 25(th) of August 2014 from Timmins, Canada. The flight ended successfully after maintaining the target altitude of 38 km for five hours. One part of the mission was a 2.5 hour underflight using a helicopter equipped with three UV light sources (LED, xenon flasher and laser) to perform an inflight calibration and examine the detectors capability to measure tracks moving at the speed of light. We describe the helicopter laser system and details of the underflight as well as how the laser tracks were recorded and found in the data. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. Finally, we present a first reconstruction of the direction of the laser tracks relative to the detector.
Keywords: Detectors for UV; visible and IR photons; Lasers; Balloon instrumentation; Space instrumentation

Meteor studies in the framework of the JEM-EUSO program - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H. J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
We summarize the state of the art of a program of UV observations from space of meteor phenomena, a secondary objective of the JEM-EUSO international collaboration. Our preliminary analysis indicates that JEM-EUSO, taking advantage of its large FOV and good sensitivity, should be able to detect meteors down to absolute magnitude close to 7. This means that JEM-EUSO should be able to record a statistically significant flux of meteors, including both sporadic ones, and events produced by different meteor streams. Being unaffected by adverse weather conditions, JEM-EUSO can also be a very important facility for the detection of bright meteors and fireballs, as these events can be detected even in conditions of very high sky background. In the case of bright events, moreover, exhibiting some persistence of the meteor train, preliminary simulations show that it should be possible to exploit the motion of the ISS itself and derive at least a rough 3D reconstruction of the meteor trajectory. Moreover, the observing strategy developed to detect meteors may also be applied to the detection of nuclearites, exotic particles whose existence has been suggested by some theoretical investigations. Nuclearites are expected to move at higher velocities than meteoroids, and to exhibit a wider range of possible trajectories, including particles moving upward after crossing the Earth. Some pilot studies, including the approved Mini-EUSO mission, a precursor of JEM-EUSO, are currently operational or in preparation. We are doing simulations to assess the performance of Mini-EUSO for meteor studies, while a few meteor events have been already detected using the ground-based facility EUSO-TA.
Keywords: Meteors; Nuclearites; JEM-EUSO; Mini-EUSO; EUSO-TA

Neutrino Target-of-Opportunity Observations with Space-based and Suborbital Optical Cherenkov Detectors - Venters, Tonia M.; Reno, Mary Hall; Krizmanic, John F.; Olinto, A. V.; Adams, J. H.; Aloisio, R.; Anchordoqui, L. A.; Anzalone, A.; Bagheri, M.; Barghini, D.; Battisti, M.; Bergman, D. R.; et al. (Proceedings of Science, 2022)
Cosmic-ray accelerators capable of reaching ultra-high energies are expected to also produce very-high energy neutrinos via hadronic interactions within the source or its surrounding environment. Many of the candidate astrophysical source classes are either transient in nature or exhibit flaring activity. Using the Earth as a neutrino converter, suborbital and space-based optical Cherenkov detectors, such as POEMMA and EUSO-SPB2, will be able to detect upward-moving extensive air showers induced by decaying tau-leptons generated from cosmic tau neutrinos with energies ∼ 10 PeV and above. Both EUSO-SPB2 and POEMMA will be able to quickly repoint, enabling rapid response to astrophysical transient events. We calculate the transient sensitivity and sky coverage for both EUSO-SPB2 and POEMMA, accounting for constraints imposed by the Sun and the Moon on the observation time. We also calculate both detectors' neutrino horizons for a variety of modeled astrophysical neutrino fluences. We find that both EUSO-SPB2 and POEMMA will achieve transient sensitivities at the level of modeled neutrino fluences for nearby sources. We conclude with a discussion of the prospects of each mission detecting at least one transient event for various modeled astrophysical neutrino sources.
CRIS-Team Scopus Importer:2024-12-16

Performances of JEM-EUSO: angular reconstruction (vol 30, pg 153, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Performances of JEM-EUSO: energy and X (max) reconstruction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory (EUSO) on-board the Japanese Experimental Module (JEM) of the International Space Station aims at the detection of ultra high energy cosmic rays from space. The mission consists of a UV telescope which will detect the fluorescence light emitted by cosmic ray showers in the atmosphere. The mission, currently developed by a large international collaboration, is designed to be launched within this decade. In this article, we present the reconstruction of the energy of the observed events and we also address the X (max) reconstruction. After discussing the algorithms developed for the energy and X (max) reconstruction, we present several estimates of the energy resolution, as a function of the incident angle, and energy of the event. Similarly, estimates of the X (max) resolution for various conditions are presented.
Keywords: JEM-EUSO; Energy reconstruction; X-max reconstruction

Science and mission status of EUSO-SPB2 - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
The Extreme Universe Space Observatory on a Super Pressure Balloon II (EUSO-SPB2) is a second generation stratospheric balloon instrument for the detection of Ultra High Energy Cosmic Rays (UHECRs, E > 1 EeV) via the fluorescence technique and of Very High Energy (VHE, E > 10 PeV) neutrinos via Cherenkov emission. EUSO-SPB2 is a pathfinder mission for instruments like the proposed Probe Of Extreme Multi-Messenger Astrophysics (POEMMA). The purpose of such a space-based observatory is to measure UHECRs and UHE neutrinos with high statistics and uniform exposure. EUSO-SPB2 is designed with two Schmidt telescopes, each optimized for their respective observational goals. The Fluorescence Telescope looks at the nadir to measure the fluorescence emission from UHECR-induced extensive air shower (EAS), while the Cherenkov Telescope is optimized for fast signals (∼10 ns) and points near the Earth's limb. This allows for the measurement of Cherenkov light from EAS caused by Earth skimming VHE neutrinos if pointed slightly below the limb or from UHECRs if observing slightly above. The expected launch date of EUSO-SPB2 is Spring 2023 from Wanaka, NZ with target duration of up to 100 days. Such a flight would provide thousands of VHECR Cherenkov signals in addition to tens of UHECR fluorescence tracks. Neither of these kinds of events have been observed from either orbital or suborbital altitudes before, making EUSO-SPB2 crucial to move forward towards a space-based instrument. It will also enhance the understanding of potential background signals for both detection techniques. This contribution will provide a short overview of the detector and the current status of the mission as well as its scientific goals.
CRIS-Team Scopus Importer:2024-12-16

Science of atmospheric phenomena with JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The main goal of the JEM-EUSO experiment is the study of Ultra High Energy Cosmic Rays (UHECR, 10(19)-10(21) e V), but the method which will be used (detection of the secondary light emissions induced by cosmic rays in the atmosphere) allows to study other luminous phenomena. The UHECRs will be detected through the measurement of the emission in the range between 290 and 430 m, where some part of Transient Luminous Events (TLEs) emission also appears. This work discusses the possibility of using the JEM-EUSO Telescope to get new scientific results on TLEs. The high time resolution of this instrument allows to observe the evolution of TLEs with great precision just at the moment of their origin. The paper consists of four parts: review of the present knowledge on the TLE, presentation of the results of the simulations of the TLE images in the JEM-EUSO telescope, results of the Russian experiment Tatiana-2 and discussion of the possible progress achievable in this field with JEM-EUSO as well as possible cooperation with other space projects devoted to the study of TLE - TARANIS and ASIM. In atmospheric physics, the study of TLEs became one of the main physical subjects of interest after their discovery in 1989. In the years 1992 - 1994 detection was performed from satellite, aircraft and space shuttle and recently from the International Space Station. These events have short duration (milliseconds) and small scales (km to tens of km) and appear at altitudes 50 - 100 km. Their nature is still not clear and each new experimental data can be useful for a better understanding of these mysterious phenomena.
Keywords: Transient Luminous Events; Elves; Sprites; Jets - Atmospheric phenomena

Space experiment TUS on board the Lomonosov satellite as pathfinder of JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
Space-based detectors for the study of extreme energy cosmic rays (EECR) are being prepared as a promising new method for detecting highest energy cosmic rays. A pioneering space device - the "tracking ultraviolet set-up" (TUS) - is in the last stage of its construction and testing. The TUS detector will collect preliminary data on EECR in the conditions of a space environment, which will be extremely useful for planning the major JEM-EUSO detector operation.
Keywords: Air-shower fluorescence telescope; JEM-EUSO; Pathfinder

The atmospheric monitoring system of the JEM-EUSO instrument - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will detect Ultra-High Energy Cosmic Rays (UHECRs) from space, detecting the UV Fluorescence Light produced by Extensive Air Showers (EAS) induced by the interaction of the cosmic rays with the earth's atmosphere. The capability to reconstruct the properties of the primary cosmic ray depends on the accurate measurement of the atmospheric conditions in the region of EAS development. The Atmospheric Monitoring (AM) system of JEM-EUSO will host a LIDAR, operating in the UV band, and an Infrared camera to monitor the cloud cover in the JEM-EUSO Field of View, in order to be sensitive to clouds with an optical depth tau a parts per thousand yen 0.15 and to measure the cloud top altitude with an accuracy of 500 m and an altitude resolution of 500 m.
Keywords: Ultra high energy cosmic rays; Atmospheric monitoring; IR camera; LIDAR

The EUSO-Balloon pathfinder - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Barrillon, P.; Batsch, T.; et al. (Experimental Astronomy, 2015)
EUSO-Balloon is a pathfinder for JEM-EUSO, the Extreme Universe Space Observatory which is to be hosted on-board the International Space Station. As JEM-EUSO is designed to observe Ultra-High Energy Cosmic Rays (UHECR)-induced Extensive Air Showers (EAS) by detecting their ultraviolet light tracks "from above", EUSO-Balloon is a nadir-pointing UV telescope too. With its Fresnel Optics and Photo-Detector Module, the instrument monitors a 50 km(2) ground surface area in a wavelength band of 290-430 nm, collecting series of images at a rate of 400,000 frames/sec. The objectives of the balloon demonstrator are threefold: a) perform a full end-to-end test of a JEM-EUSO prototype consisting of all the main subsystems of the space experiment, b) measure the effective terrestrial UV background, with a spatial and temporal resolution relevant for JEM-EUSO. c) detect tracks of ultraviolet light from near space for the first time. The latter is a milestone in the development of UHECR science, paving the way for any future space-based UHECR observatory. On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. From a float altitude of 38 km, the instrument operated during the entire astronomical night, observing UV-light from a variety of ground-covers and from hundreds of simulated EASs, produced by flashers and a laser during a two-hour helicopter under-flight.
Keywords: UHECR; Air-fluorescence; JEM-EUSO; Balloon experiment

The infrared camera onboard JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on the Japanese Experiment Module (JEM-EUSO) on board the International Space Station (ISS) is the first space-based mission worldwide in the field of Ultra High-Energy Cosmic Rays (UHECR). For UHECR experiments, the atmosphere is not only the showering calorimeter for the primary cosmic rays, it is an essential part of the readout system, as well. Moreover, the atmosphere must be calibrated and has to be considered as input for the analysis of the fluorescence signals. Therefore, the JEM-EUSO Space Observatory is implementing an Atmospheric Monitoring System (AMS) that will include an IR-Camera and a LIDAR. The AMS Infrared Camera is an infrared, wide FoV, imaging system designed to provide the cloud coverage along the JEM-EUSO track and the cloud top height to properly achieve the UHECR reconstruction in cloudy conditions. In this paper, an updated preliminary design status, the results from the calibration tests of the first prototype, the simulation of the instrument, and preliminary cloud top height retrieval algorithms are presented.
Keywords: JEM-EUSO; Space observatory; IR-camera; Ultra-High Energy Cosmic Rays (UHECR)

The JEM-EUSO mission: An introduction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Pernas, M. Ave; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on board the Japanese Experiment Module of the International Space Station, JEM-EUSO, is being designed to search from space ultra-high energy cosmic rays. These are charged particles with energies from a few 10(19) eV to beyond 10(20) eV, at the very end of the known cosmic ray energy spectrum. JEM-EUSO will also search for extreme energy neutrinos, photons, and exotic particles, providing a unique opportunity to explore largely unknown phenomena in our Universe. The mission, principally based on a wide field of view (60 degrees) near-UV telescope with a diameter of similar to 2.5 m, will monitor the earth's atmosphere at night, pioneering the observation from space of the ultraviolet tracks (290-430 nm) associated with giant extensive air showers produced by ultra-high energy primaries propagating in the earth's atmosphere. Observing from an orbital altitude of similar to 400 km, the mission is expected to reach an instantaneous geometrical aperture of A (g e o) a parts per thousand yen 2 x 10(5) km(2) sr with an estimated duty cycle of similar to 20 %. Such a geometrical aperture allows unprecedented exposures, significantly larger than can be obtained with ground-based experiments. In this paper we briefly review the history of space-based search for ultra-high energy cosmic rays. We then introduce the special issue of Experimental Astronomy devoted to the various aspects of such a challenging enterprise. We also summarise the activities of the on-going JEM-EUSO program.
Keywords: Ultra-high energy cosmic rays; Neutrinos

The JEM-EUSO observation in cloudy conditions - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO (Extreme Universe Space Observatory on-board the Japanese Experiment Module) mission will conduct extensive air shower (EAS) observations on the International Space Station (ISS). Following the ISS orbit, JEM-EUSO will experience continuous changes in the atmospheric conditions, including cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate from both EAS property and cloud climatology points of view. In the present work, the impact of clouds on the apparent profile of EAS is demonstrated through the simulation studies, taking into account the JEM-EUSO instrument and properties of the clouds. These results show a dependence on the cloud-top altitude and optical depth of the cloud. The analyses of satellite measurements on the cloud distribution indicate that more than 60 % of the cases allow for conventional EAS observation, and an additional similar to 20 % with reduced quality. The combination of the relevant factors results in an effective trigger aperture of EAS observation similar to 72 %, compared to the one in the clear atmosphere condition.
Keywords: JEM-EUSO; Ultra-high energy cosmic ray; Extensive air shower

The Large Observatory For x-ray Timing - Feroci, Marco; Den Herder, J. W.; Bozzo, E.; Barret, D.; Brandt, Soren; Hernanz, Margarita; Van Der Klis, M.; Pohl, M.; Santangelo, A.; Stella, L.; Watts, A.; Wilms, Jörn; et al. (2014)
The Large Observatory For x-ray Timing (LOFT) was studied within ESA M3 Cosmic Vision framework and participated in the final downselection for a launch slot in 2022-2024. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument, LOFT will study the behaviour of matter under extreme conditions, such as the strong gravitational field in the innermost regions of accretion flows close to black holes and neutron stars, and the supranuclear densities in the interior of neutron stars. The science payload is based on a Large Area Detector (LAD, 10 m(2) effective area, 2-30 keV, 240 eV spectral resolution, 1 degrees collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g. GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the status of the mission at the end of its Phase A study.
Keywords: X-ray timing; X-ray spectroscopy; X-ray imaging; compact objects; X-ray detectors; microchannel plates

The LOFT mission concept: A status update - Feroci, M.; Bozzo, E.; Brandt, S.; Hernanz, M.; Van Der Klis, M.; Liu, L. P.; Orleanski, P.; Pohl, M.; Santangelo, A.; Schanne, S.; Stella, L.; Takahashi, T.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The Large Observatory For x-ray Timing (LOFT) is a mission concept which was proposed to ESA as M3 and M4 candidate in the framework of the Cosmic Vision 2015-2025 program. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument and the uniquely large field of view of its wide field monitor, LOFT will be able to study the behaviour of matter in extreme conditions such as the strong gravitational field in the innermost regions close to black holes and neutron stars and the supra-nuclear densities in the interiors of neutron stars. The science payload is based on a Large Area Detector (LAD, >8m effective area, 2-30 keV, 240 eV spectral resolution, 1 degree collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g., GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the current technical and programmatic status of the mission.
Keywords: Silicon detectors; spectroscopy; timing; X-ray astronomy

Towards observations of nuclearites in Mini-EUSO - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Ave Pernas, M.; et al. (Proceedings of Science, 2022)
Mini-EUSO is a small orbital telescope with a field of view of 44◦ × 44◦, observing the night-time Earth mostly in 320-420 nm band. Its time resolution spanning from microseconds (triggered) to milliseconds (untriggered) and more than 300 × 300 km of the ground covered, already allowed it to register thousands of meteors. Such detections make the telescope a suitable tool in the search for hypothetical heavy compact objects, which would leave trails of light in the atmosphere due to their high density and speed. The most prominent example are the nuclearites – hypothetical lumps of strange quark matter that could be stabler and denser than the nuclear matter. In this paper, we show potential limits on the flux of nuclearites after collecting 42 hours of observations data.
CRIS-Team Scopus Importer:2024-12-16

Ultra high energy photons and neutrinos with JEM-EUSO (vol 40, pg 215, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Ultra-violet imaging of the night-time earth by EUSO-Balloon towards space-based ultra-high energy cosmic ray observations - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2019)
The JEM-EUSO (Joint Experiment Missions for the Extreme Universe Space Observatory) program aims at developing Ultra-Violet (UV) fluorescence telescopes for efficient detections of Extensive Air Showers (EASs) induced by Ultra-High Energy Cosmic Rays (UHECRs) from satellite orbit. In order to demonstrate key technologies for JEM-EUSO, we constructed the EUSO-Balloon instrument that consists of a ∼1 m 2 refractive telescope with two Fresnel lenses and an array of multi-anode photo-multiplier tubes at the focus. Distinguishing it from the former balloon-borne experiments, EUSO-Balloon has the capabilities of single photon counting with a gate time of 2.3 µs and of imaging with a total of 2304 pixels. As a pathfinder mission, the instrument was launched for an 8 h stratospheric flight on a moonless night in August 2014 over Timmins, Canada. In this work, we analyze the count rates over ∼2.5 h intervals. The measurements are of diffuse light, e.g. of airglow emission, back-scattered from the Earth's atmosphere as well as artificial light sources. Count rates from such diffuse light are a background for EAS detections in future missions and relevant factor for the analysis of EAS events. We also obtain the geographical distribution of the count rates over a ∼780 km 2 area along the balloon trajectory. In developed areas, light sources such as the airport, mines, and factories are clearly identified. This demonstrates the correct location of signals that will be required for the EAS analysis in future missions. Although a precise determination of count rates is relevant for the existing instruments, the absolute intensity of diffuse light is deduced for the limited conditions by assuming spectra models and considering simulations of the instrument response. Based on the study of diffuse light by EUSO-Balloon, we also discuss the implications for coming pathfinders and future space-based UHECR observation missions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Airglow; EUSO-Balloon; Extensive air shower; JEM-EUSO; Ultra-high energy cosmic ray